Lignin Metabolism Is Crucial in the Plant Responses to Tambocerus elongatus (Shen) in Camellia sinensis L. - Wenli Wang; Xiaogui Zhou; Qiang Hu; Qiuhong Wang; Yanjun Zhou; Jingbo Yu; Shibei Ge; Lan Zhang; Huawei Guo; Meijun Tang; Xin Li (Plants)
Tambocerus elongatus (Shen) (Hemiptera: Cicadellidae) is a devastating insect pest species of Camellia sinensis, significantly affecting the yield and quality of tea. Due to growing concerns over the irrational use of insecticides and associated food safety, it is crucial to better understand the innate resistance mechanism of tea trees to T. elongatus. This study aims to explore the responses of tea trees to different levels of T. elongatus infestation. We first focused on the primary metabolism and found that the amino acid levels decreased significantly with increasing T. elongatus infestation, while sugar accumulation showed an opposite trend. Moreover, secondary metabolite analysis showed a significant increase in flavonoid compounds and lignin content after T. elongatus infestation. Metabolomics analysis of the flavonoid compounds revealed a decrease in the proanthocyanidin level and an increase in anthocyanidin glycosides (anthocyanins and their derivatives) after T. elongatus infestation. T. elongatus infestation also caused a decrease in the abundance of non-ester catechins and an increase in the abundance of ester catechins. Furthermore, the gene expression analysis revealed that transcripts of genes involved in flavonoid biosynthesis, such as CsCHI, CsF3H, CsF3′H, CsFNS, CsFLS, and CsUFGT, were down-regulated, while genes involved in the lignin pathway were up-regulated by insect infestation, suggesting that lignin probably plays a pivotal role in tea plant response to T. elongatus infestation. Analysis of the expression of related genes indicates that the jasmonate (JA) pathway primarily responds to leafhopper damage. These findings suggest that the lignin pathway and JA play a preferential role in tea plant response to T. elongatus. Furthermore, the production of saccharides and the accumulation of anthocyanin glycosides in the flavonoid metabolic pathway are critical during this stress response. Further exploration of the roles of anthocyanin glycosides and lignin in tea tree resistance could provide a theoretical basis for understanding the defense mechanism of tea trees against T. elongatus damage.